Delay-dependent guaranteed cost gain-scheduling control of LPV state-delayed systems - Kucukdemiral, I. B. (WILEY, 2008)
Delay-dependent gain-scheduling controller design problem is addressed for the linear parameter-varying state-delayed systems with time-varying delays. By choosing a Lyapunov-Krakovskii functional, delay-dependent conditions for the existence of guaranteed cost gain-scheduling controller are obtained. Besides, an algorithm is also presented to solve resultant nonconvex matrix inequalities in terms of linear matrix inequalities. Finally, three numerical examples with simulations are illustrated in order to demonstrate the validity of the proposed method. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: time-delayed systems; guaranteed cost control; gain-scheduling control; linear matrix inequalities; NEUTRAL SYSTEMS; LMI APPROACH; TIME-DELAY; STABILITY; STABILIZATION; Automation & Control Systems; Operations Research & Management Science; Mathematics